XMN-Newton observations of toothbrush cluster of galaxies - Kara, Sinancan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Clusters of galaxies are the largest gravitationally bound systems in the Uni verse. Their immense gravitational potential holds 10’s to 100’s bright galaxies and also an intracluster medium (ICM) surrounding them. ICM gets enriched by supernova explosions and is heated up to the temperatures of 107 to 108 K by the gravitational potential well, which causes X-ray emission. The merging cool-core cluster 1RXSJ0603.3+4213 (z=0.225) shows a large radio relic associated with a merger shock north of its core. Because the shape of the radio relic is similar to a toothbrush, the cluster is nicknamed as ”Toothbrush”. Our aim is to investigate the metal abundance and produce a temperature map by using 82 ks X-ray observation of XMM-Newton in order to ﬁnd how the shock aﬀects parameters radially.
Keywords: Galaxies.